Cranial Anatomy of the Caseid Synapsid Cotylorhynchus romeri, a Large Terrestrial Herbivore From the Lower Permian of Oklahoma, U.S.A - Reisz, Robert R.; Scott, Diane; Modesto, Sean P. (Frontiers in Earth Science, 2022)
The detailed description of the cranial anatomy of Cotylorhynchus romeri, a very large caseid synapsid from the lower Permian Hennessey Formation of Oklahoma uncovered several potential autapomorphies, including parietal-postorbital contact greatly reduced by broad anterior process of supratemporal; the postparietals are transversely broad and contact the supratemporals laterally; the quadratojugal has a pennant-like occipital process; the stapes has a short shaft and a ventral process that abuts against the palate; the bulbous marginal dentition narrows distally and carries three small denticles; the vomer has three large teeth along its medial edge; (teeth on body of parasphenoid) and the surangular overlaps the posterodorsal tip of the dentary and excludes it from the coronoid eminence. Owing to lack of comparative cranial material in most large caseids, the evolutionary history of these autapomorphies remains ambiguous because they cannot be determined in the closest relatives of Cotylorhynchus romeri. The recent hypothesis that Cotylorhynchus romeri was primarily aquatic was proposed on a paleobiological basis that ignored paleontological and taphonomic evidence from the Hennessey Formation. Autochthonous preservation of several articulated skeletons of Cotylorhynchus romeri in subaerially deposited sediments that also preserve ‘swarms’ of an aestivating fossil amphibian (Lysorophus) indicate that this caseid was the largest tetrapod of a terrestrial fauna that lived in a monsoonal climate.